Adaptive Organizational Change Management: A Risk-Responsive Framework for Economic Uncertainty (European Journal of Marketing and Economics, 2025)
In an era of heightened economic volatility, effective risk management has become a cornerstone of organizational resilience and strategic agility. This study investigates how external market disruptions and internal operational complexities influence the selection and efficacy of change-management approaches. By systematically analyzing risk-assessment frameworks, we reveal how aligning an organization’s risk profile with its resources, capabilities, and strategic objectives enables the development of tailored action plans—mitigating threats while leveraging emerging opportunities. The research highlights the critical interplay between corporate strategy, organizational culture, firm size, and partnership networks, demonstrating their collective impact on the success of change initiatives. Building on diagnostic insights, we propose a risk-responsive organizational development model designed to enhance adaptability and ensure sustainable transformation. Our findings provide leaders with a structured roadmap for embedding economic risk analysis into every phase of change management, fostering resilience in dynamic business environments.